The Influence of Fuel (Pertalite) Scarcity on the Economic Turnover of the Community in Desa Tela, Pulau-Pulau Babar District - Lukmetiabla, Eva Gizela; Papilaya, Josef (JENDELA PENGETAHUAN, 2025)
This study aims to analyze the impact of fuel (Pertalite) scarcity on the economic turnover of the community in Desa Tela, Pulau-Pulau Babar District. Fuel is a critical component in various economic activities, particularly in the transportation and goods distribution sectors. The scarcity of fuel can significantly increase operational costs and the prices of goods, thus affecting the economic turnover in the local community. This research employs a quantitative approach by distributing questionnaires to 50 respondents in Desa Tela. The collected data were analyzed using simple linear regression to assess the relationship between fuel scarcity and economic turnover. The findings reveal that fuel scarcity has a significant effect on the economic turnover of the community, with the impact primarily felt in sectors heavily dependent on energy. Therefore, government intervention is required to address fuel scarcity issues, such as building adequate energy infrastructure to maintain local economic stability